2003
DOI: 10.1002/path.1325
|View full text |Cite
|
Sign up to set email alerts
|

Concerted promoter hypermethylation of hMLH1, p16INK4A, and E‐cadherin in gastric carcinomas with microsatellite instability

Abstract: In most sporadic gastric carcinomas, microsatellite instability (MSI) originates from inactivation of the hMLH1 gene by promoter hypermethylation. However, the methylation patterns of other genes and their consequences in high MSI (MSI-H) gastric carcinomas are not well characterized. To address the aberrant promoter methylation profiles of MSI-H gastric carcinomas, promoter methylation of six genes (hMLH1, p16(INK4A), E-cadherin, Rb, RASSF1A, and VHL) and CpG island methylator phenotype (CIMP) were explored i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 34 publications
2
57
0
1
Order By: Relevance
“…The present study demonstrates no significant difference in the proportion of MSI between the differentiated type and the undifferentiated type. Although predominant intestinal-type histology in microsatellite-unstable carcinomas has been widely accepted [2,4,5,9,10,23], several reports have shown predominant poorly differentiated histology [1], or no significant association between histological morphology and MSI [6,[11][12][13]. The differences among these reports were considered to depend upon the specific groups of cases studied and the type and number of markers examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrates no significant difference in the proportion of MSI between the differentiated type and the undifferentiated type. Although predominant intestinal-type histology in microsatellite-unstable carcinomas has been widely accepted [2,4,5,9,10,23], several reports have shown predominant poorly differentiated histology [1], or no significant association between histological morphology and MSI [6,[11][12][13]. The differences among these reports were considered to depend upon the specific groups of cases studied and the type and number of markers examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, several issues remain poorly defined and are the subject of much debate because of several reports showing predominant poorly differentiated histology [1] or no significant association between histological morphology and MSI [6,[11][12][13]. Because most previous reports were not concerned with histological subtype, but rather with Lauren's classification, a relationship between the histological subtypes of gastric carcinomas and MSI remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The hypermethylation of CpG islands within the promoter and/or upstream exon regions is an important epigenetic mechanism underlying the inactivation of tumor-suppressor genes (TSGs) [3] . It was reported that quite a few TSGs, including the Ras association domain family 1A (RASSF1A) gene, are epigenetically silenced by aberrant promoter hypermethylation in gastric and colorectal cancer [4][5][6][7][8][9][10] . RASSF1A is a newly identified candidate TSG located in the 3p21.3 region [11] , and promoter hypermethylation of RASSF1A, which is its most common inactivation mechanism, has been observed in many human solid tumors, including gastric and colorectal cancers [11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The CpG island methylation phenotype (CIMP) is an epigenetic phenomenon found in a variety of cancers. 19,20 In colorectal and gastric cancers, CIMP frequently associates with MLH1 methylation, loss of MLH1 transcription, and MSI-H. 19,21,22 An association of CIMP with BRAF mutations has been found in colorectal cancer 23 but, interestingly, mutations in BRAF do not have a significant role in either CIMP-positive or -negative gastric cancers. 24 Analyses of genomic and epigenetic interrelations in human neoplasms have added largely to our understanding of tumor development and have led to a novel molecular classification of colorectal cancer.…”
mentioning
confidence: 99%